Small photosynthetic flagellates of the White Sea: seasonal dynamics and role in plankton and ice communities - E. Nikishova R.; I. Radchenko G.; T. Belevich A.; Е. Никишова Р.; И. Радченко Г.; Т. Белевич А. (Lomonosov Moscow State University, School of Biology, 2020)
Abundance and biomass of small photosynthetic flagellates (SPF; 3–10 µm), chlorophyll a, and the contribution of SPF to total phytoplankton biomass in different stages of seasonal succession in ice and the surface water were studied in Kandalaksha Bay of the White Sea in September 2016, February and July 2017. In summer SPF biomass in the photic layer averaged 38.36±9.77 mg С/м3, in autumn – 2.22±1.43 mg С/м3, in under-ice water – 2.6±1.72 mg С/м3, and in ice – 14.79±11.25 mg С/м3. The contribution of SPF to total phytoplankton biomass depends of the season and ranged from 29% to 95%, the contribution to sympagic communities averaged 66%. The size structure of photosynthetic flagellates varied by seasons. Flagellates with cell size 6–10 µm dominated in summer plankton and in the ice. Flagellates with cell size 3–6 µm prevailed in autumn and in the under-ice water. The obtained data of SPF abundance gave higher values of the total phytoplankton biomass of the White Sea in the autumn-winter period compared with the estimates obtained previously. Applying the method of epifluorescence microscopy confirms the assumption that photosynthetic flagellates are the main producers in the winter period, as well as in the summer when the biomass of planktonic algae with cell size more than 10 µm is low.more than 10 µm is low. Численность и биомасса мелких (3–10 мкм) фототрофных флагеллят (МФФ), концентрация хлорофилла «а», а также вклад МФФ в суммарную биомассу фитопланктона на разных этапах сезонного развития во льду и поверхностном слое воды были исследованы в Кандалакшском заливе Белого моря в сентябре 2016 г., а также в феврале и июле 2017 г. Биомасса МФФ в поверхностном слое составила в среднем летом 38,36±9,77 мг С/м3, осенью – 2,22±1,43 мг С/м3, зимой в подледной воде – 2,6±1,72 мг С/м3, во льду – 14,79±11,25 мг С/м3. Вклад МФФ в суммарную биомассу фитопланктона колебался в зависимости от сезона от 29% до 95%, вклад в криофлору составил в среднем 66%. Размерная структура МФФ различалась по сезонам. Летом и зимой во льду доминировали флагелляты с размером клетки от 6 до 10 мкм. Осенью и в подледной воде среди МФФ преобладала размерная группа от 3 до 6 мкм. Полученные оценки обилия МФФ обусловили более высокие значения суммарной биомассы фитопланктона Белого моря в осенне-зимний период по сравнению с оценками, полученными ранее. Учет МФФ современным методом эпифлуоресцентной микроскопии подтверждает предположение о том, что основными продуцентами в зимний период, а также летом при низкой биомассе планктонных водорослей размерной фракции более 10 мкм являются МФФ.